2022
DOI: 10.3390/su14137711
|View full text |Cite
|
Sign up to set email alerts
|

Application of the EFQM Model in the Education Institution for Driving Improvement of Processes towards Sustainability

Abstract: Effective process management is a basic prerequisite for increasing the quality and performance of educational organizations. The aim of the paper is to point out the potential for the application of the European Foundation for Quality Management (EFQM) Model 2020 to improve and perfect the processes in a Slovakian vocational school towards sustainability. We used the latest version of the EFQM Model and applied the questionnaire method to conduct a self-assessment. A study of the documentation was also carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
4
3
2
Order By: Relevance
“…It is also consistent with the results of the studies of (Faraj, 2020; Abdel Fattah, 2020; Al-Anzi, 2020), which concluded that the level of commitment and application of the leadership standard was also medium. This result differs from the results of the study (Sütoová et al, 2022), which found a weakness in the organizational culture standard. Also, item (6) stipulating "The university develops plans to develop its administrative leadership based on evaluation indicators" is ranked first to emphasize that universities develop plans to develop their administrative leadership based on evaluation indicators.…”
Section: Second: Results Related To the Second Research Domain "Organ...contrasting
confidence: 99%
See 4 more Smart Citations
“…It is also consistent with the results of the studies of (Faraj, 2020; Abdel Fattah, 2020; Al-Anzi, 2020), which concluded that the level of commitment and application of the leadership standard was also medium. This result differs from the results of the study (Sütoová et al, 2022), which found a weakness in the organizational culture standard. Also, item (6) stipulating "The university develops plans to develop its administrative leadership based on evaluation indicators" is ranked first to emphasize that universities develop plans to develop their administrative leadership based on evaluation indicators.…”
Section: Second: Results Related To the Second Research Domain "Organ...contrasting
confidence: 99%
“…Moreover, this result differs from the results of the study (Sütoová et al, 2022), which found a weakness in the criterion of stakeholder perceptions. The arithmetic means and standard deviations for the sample members' point of view ranged between (3.895) and (2.919), which is between high and medium.…”
Section: 147 Mediumcontrasting
confidence: 99%
See 3 more Smart Citations